Burkholderia pseudomallei short-chain dehydrogenase/ oxidoreductase: potential urine biomarker candidate for acute melioidosis - Pakeer, Aniza; Mariappan, Vanitha Mariappan; How, Soon Hin; Mustafa Mahmoud, Mohammed Imad Al-Deen (IIUM Press, 2021)
INTRODUCTION: In the current climate of urgency in identifying biomarkers for the development of rapid diagnostic kits, the use of urine samples to diagnose acute melioidosis was evaluated, comparing urine samples from Burkholderia pseudomallei culture-positive and culture-negative patients, and comparing pneumonic and septicemic melioidosis. MATERIAL AND METHODS: Eleven urine samples from clinically suspected melioidosis patients from a tertiary referral center, Hospital Tengku Ampuan Afzan, Pahang was used. An in-solution method for the detection of bacterial proteins using liquid chromatography-mass spectrometry quadrupole time-of-flight (LCMS QTOF) was used. RESULTS: Three bacterial proteins were consistently detected among all the culture[1]positive and PCR-positive cases tested, namely SDR family NAD(P)-dependent oxidoreductase protein (32kDa), 3-hydroxyacyl-CoA dehydrogenase Burkholderia sp. (32kDa), and NAD(P)-dependent dehydrogenase (short-subunit alcohol dehydrogenase family) Burkholderia sp. (33kDa). CONCLUSIONS: Short-chain dehydrogenase (SDO) proteins could potentially be a urine biomarker candidate as these have shown to aid in the ability of Burkholderia spp. to invade host cells as this action is important for the initial intracellular survival of the organism.